Magnesium-based nanocomposites for orthopedic applications: A review - Meng Cheng; Xigang Liang; Lihua Cui; Dongyan Guan; Yang Qu; Jianwu Zhao; Kai Guan (Journal of Magnesium and Alloys)
Mg-based materials have potential applications in the field of orthopedics owing to their good biodegradability, biocompatibility, and bone-inducing properties. However, during the early application process, their major drawback was rapid degradation rate, which limited their clinical application. Nanoparticles can effectively reinforce the mechanical strength and corrosion resistance of Mg matrices, and different nanoparticles can be selected to achieve different biological functions. Therefore, Mg-based nanocomposites have emerged as a versatile class of degradable implant materials with broad clinical potential. This review summarizes the research progress of Mg-based orthopedic implants, mainly including the reinforcement mechanism of nanoparticles on Mg-based materials, the effects and biological functions of different nanoparticle enhancers, surface modification, and the application of new manufacturing technologies. Furthermore, the degradation process of Mg-based materials and the biological functions of magnesium ion (Mg2+) during the degradation process are discussed in detail. We focused on the biological mechanisms through which Mg2+ promotes bone and vascular formation and inhibits osteoclasts by regulating the immune microenvironment or multiple signaling pathways. Finally, the clinical application of Mg-based orthopedic implants are introduced and the future research directions of Mg-based nanocomposites are discussed.